Do healthy older adults use SNS? Focus on LINE, Facebook, Twitter (now X), and Instagram - Kanon Tsukada; Tomoya Takahashi; Yuho Shimizu; Yan Li; Toshihito Tsuchiya; Kiyo Kawakubo; Tomoya Sagara; Koki Ito; Tomoki Furuya; Hiroyuki Suzuki (Archives of Gerontology and Geriatrics Plus)
Background: The use of social networking services (SNS) by older adults within the context of the digital divide has become a hot topic. Several studies have shown that SNS use among older adults is related to their health status; however, few studies have examined the association between health and specific SNS platforms. Objective: This study investigates the relationship between older adults’ use of four major SNS platforms in Japan (LINE, Facebook, Twitter [now X], and Instagram) and the health of older adults. Subjective health and frequency of going out were used as health indicators. Method: A survey was conducted among participants in a health promotion program for older adults in Tokyo between 2020 and 2022. A total of 391 older adults participated in the study (M = 72.11 years, 65–86 years, 363 women). Results: Logistic regression analysis revealed that subjective health was higher in users of Facebook, Twitter [now X], and Instagram (but not LINE) compared to non-users. Frequency of going out was not associated with SNS use. Conclusions: Older adults with higher subjective health may be more likely to use SNS platforms due to their willingness to learn new skills and actively participate in social activities. Additionally, SNS may help improve the health of older adults by enabling communication with distant family and friends, even for those who are unable to go out frequently due to health problems.